2018
DOI: 10.1088/1741-4326/aacf47
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear wave interactions generate high-harmonic cyclotron emission from fusion-born protons during a KSTAR ELM crash

Abstract: The radio frequency detection system on the KSTAR tokamak has exceptionally high spectral and temporal resolution. This enables measurement of previously undetected fast plasma phenomena in the ion cyclotron range of frequencies. Here we report and analyse a novel spectrally structured ion cyclotron emission (ICE) feature in the range 500 MHz to 900 MHz, which exhibits chirping on sub-microsecond timescales. Its spectral peaks correspond to harmonics l of the proton cyclotron frequency f cp at the outer midpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(76 citation statements)
references
References 46 publications
4
72
0
Order By: Relevance
“…[36]. Previous MCI simulations of KSTAR plasma conditions have similarly shown that MCI excited waves in the same frequency range can also give rise to experimentally observed features above the lower hybrid frequency [41]. This excitation of waves at high and low frequencies due to nonlinear wave-wave coupling is now routinely observed in PIC simulations of the MCI such as those presented in here.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…[36]. Previous MCI simulations of KSTAR plasma conditions have similarly shown that MCI excited waves in the same frequency range can also give rise to experimentally observed features above the lower hybrid frequency [41]. This excitation of waves at high and low frequencies due to nonlinear wave-wave coupling is now routinely observed in PIC simulations of the MCI such as those presented in here.…”
Section: Discussionsupporting
confidence: 77%
“…The simulation is set up in slab geometry, corresponding to the local approximation; it does not incorporate any toroidal effects or eigenmode structure [32,33,34,48,49,50,51,52,53,54,55]. The omission of toroidal effects is expected to have only marginal consequences for modelling the ICE phenomenology addressed here, given the success of calculations and computations that use the local approximation in explaining results from JET and TFTR [1,2,4,3,7,38,36], as well as more recent ICE observations from KSTAR [40,41,42] and LHD [56,44].…”
Section: Computational Approach and Simulation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, even the enhanced spreading of parti- Note that ghost chirps have also been reported in other studies. For instance, see the recent analysis of ghost features in ion cyclotron emission (ICE) spectra [58].…”
Section: C4 Ghost Chirps and Resonance Overlapmentioning
confidence: 99%